Cambodian Rice: The Hidden Heavyweight in Global Trade - Funan Techo Canal as a Catalyst for Direct Exports - Mirzabaev, Alisher; Zwinger, Jeremy (International Rice Research Institute, 2025)
• Cambodia’s rice exports have surged over the past decade, reaching more than 5 MMT of paddy trade in 2025, with plans to expand milled rice exports beyond 1 MMT despite current logistics and milling constraints—positioning the country among the world’s top five exporters, and climbing. • The Kingdom has earned global recognition for quality, winning the World’s Best Rice award multiple times over the last decade. • National strategy prioritizes shifting from raw paddy exports to domestic milling, certification, and branding, ensuring more of the export value is captured within Cambodia. • The government is pursuing an ambitious strategy to strengthen the rice industry, with initiatives such as the Funan Techo Canal, which is expected to cut logistics costs and potentially enable direct exports of 5–6MMT of milled rice annually by the 2030s.